2019
DOI: 10.1016/j.jsames.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

New remains of Nothrotheriinae (Mammalia, Xenarthra) from Late Pleistocene fluvial deposits of Northern Pampa (Santa Fe Province, Argentina)

Abstract: In this contribution the record of a Nothrotheriinae (Xenarthra, Tardigrada) ground sloth is reported from the Late Pleistocene of the Northern Pampa of Santa Fe Province, Argentina. The stratigraphic unit where the fossil was collected corresponds to fluvial-palustrine sediments of the Timbúes Formation, outcropping along the Carcarañá River valley. The relative stratigraphic position of this lithostratigraphic unit, observed in several sections mainly on the Paraná River cliffs near Carcarañá River distal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…), Nothrotheriinae is represented by Nothrotherium from Brazil, Argentina and Uruguay (Kraglievich ; de Paula Couto ; Perea ; Vezzosi et al . ), Nothrotheriops from the United States, Belize and Mexico (De Iuliis et al . ), and Nothropus from Santa Fe Province (Argentina) and Bolivia (Burmeister ; Bordas ; Quiñones et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…), Nothrotheriinae is represented by Nothrotherium from Brazil, Argentina and Uruguay (Kraglievich ; de Paula Couto ; Perea ; Vezzosi et al . ), Nothrotheriops from the United States, Belize and Mexico (De Iuliis et al . ), and Nothropus from Santa Fe Province (Argentina) and Bolivia (Burmeister ; Bordas ; Quiñones et al .…”
Section: Discussionmentioning
confidence: 99%
“…() and Vezzosi et al . () indicated that Nothrotheriinae were capable of inhabiting a much wider range of habitats and climates ranging from cold and arid to warm and humid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations